SIFAT VENIR DAN KAYU LAPIS 9 JENIS KAYU DARI JAWA BARAT - M I lskandar; Suwandi Kliwon; Paribotro Sutigno (Pusat Penelitian dan Pengembangan Hasil Hutan, 1991)
A study result on the suitability of 9 wood species from West Java as raw material for veneer and plywood is reported in this paper study conaisted of log peeling characteristic, veneer property and some physical/ mechanical properties of plywood (triplex and multiplex):All of the logs from 9 wood species could be peeled in cold condition, producing 1.5 mm veneer at a cuting angle between 90°30-91°30. The average shrinkage of veneer is 7.21%, with a minimum of 4.08% (Enteroloblum) and maximum 10. 75% (keruing). Veneer swelling from oven-dry to air-dry condition varied between 2.04% (Enterolobium) and 4.28% (Damar) with an average of 2.93%.The bonding strength of plywood from 6 wood species (66%.) conform with the Indonesian standard fo type 11 or water resistant, all wood species conform with Japanese and German standard.The specific gravity of multiplex (0,60) is higher than triplex (0,58). Some mechanical properties of multiplex are higher than triplex.